Cerebellum to motor cortex paired associative stimulation induces bidirectional STDP-like plasticity in human motor cortex - Lu, Ming-Kuei; Tsai, Chon-Haw; Ziemann, Ulf (Frontiers in Human Neuroscience, 2012)
The cerebellum is crucially important for motor control and motor adaptation. Recent non-invasive brain stimulation studies have indicated the possibility to alter the excitability of the cerebellum and its projections to the contralateral motor cortex, with behavioral consequences on motor control and motor adaptation. Here we sought to induce bidirectional spike-timing dependent plasticity (STDP)-like modifications of motor cortex (M1) excitability by application of paired associative stimulation (PAS) in healthy subjects. Conditioning stimulation over the right lateral cerebellum (CB) preceded focal TMS of the left M1 hand area at an interstimulus interval of 2 ms (CB→M1 PAS2ms), 6 ms (CB→M1 PAS6ms) or 10 ms (CB→M1 PAS10ms) or randomly alternating intervals of 2 and 10 ms (CB→M1 PASControl). Effects of PAS on M1 excitability were assessed by the motor evoked potential (MEP) amplitude, short-interval intracortical inhibition (SICI), intracortical facilitation (ICF) and cerebellar-motor cortex inhibition (CBI) in the first dorsal interosseous muscle of the right hand. CB→M1 PAS2ms resulted in MEP potentiation, CB→M1 PAS6ms and CB→M1 PAS10ms in MEP depression, and CB→M1 PASControl in no change. The MEP changes lasted for 30-60 min after PAS. SICI and CBI decreased non-specifically after all PAS protocols, while ICF remained unaltered. The physiological mechanisms underlying these MEP changes are carefully discussed. Findings support the notion of bidirectional STDP-like plasticity in M1 mediated by associative stimulation of the cerebello-dentato-thalamo-cortical pathway and M1. Future studies may investigate the behavioral significance of this plasticity.